Copper-based metal-organic framework materials, methods of making and applications thereof

CN119613742BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311177189.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2026-10-16
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

[0008]2021年,Liqiang Mai等(DOI:10.1002/anie.202112116)制备出含缺陷的Cu-BTC,结构单元为Cu-O3配位的轮浆状Cu二聚体,低配位活性位点大幅提升了产物烃组分选择性,其中乙烯的法拉第效率低于35%

Benefits of technology

[0024] The beneficial effects of the present invention through the above technical solution include:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613742B_ABST
    Figure CN119613742B_ABST
Patent Text Reader

Abstract

The application relates to the field of metal organic framework material preparation, and discloses a copper-based metal organic framework material and a preparation method and application thereof. The copper-based metal organic framework material has a honeycomb-like spherical morphology; the metal element in the metal organic framework material is copper; the organic ligand in the metal organic framework material is uniform benzenetricarboxylic acid; wherein the diameter of the spherical particle of the metal organic framework material is 0.8-8 microns. The copper-based metal organic framework material is used in the reaction of electrocatalytic reduction of carbon dioxide to ethylene, and has a relatively high ethylene faradaic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal-organic framework material preparation, specifically to a copper-based metal-organic framework material, its preparation method, and its application. Background Technology

[0002] Currently, the development of human industrial civilization has led to excessive emissions of the greenhouse gas carbon dioxide, ultimately resulting in a series of environmental problems. Global warming, ocean acidification, melting polar glaciers, and rising sea levels are all related to excessive carbon dioxide emissions. Atmospheric carbon dioxide levels have increased from 280 ppm before the Industrial Revolution to 421 ppm in 2022. Therefore, carbon emissions have become an increasingly important focus of attention. Electrocatalytic carbon dioxide reduction technology (which reduces carbon dioxide to fuels or chemicals such as carbon monoxide, formic acid, methane, ethylene, ethanol, acetic acid, and n-propanol) reduces carbon dioxide levels and converts it for utilization, achieving a carbon cycle. Ethylene, with its high energy density and market value, is an important chemical raw material, and carbon dioxide reduction to ethylene has a promising application prospect. However, the carbon dioxide reduction to ethylene pathway involves C-C coupling and multi-electron and proton transfer, and current catalysts still face shortcomings such as low catalytic activity, low selectivity, and poor stability.

[0003] Metal-based materials are the most common electrocatalytic catalysts for the reduction of carbon dioxide, with copper-based materials being the most suitable for producing multi-carbon components such as ethylene and ethanol. However, due to limitations such as C / C coupling, multiple electron and proton transfer, and competitive hydrogen evolution reactions, current copper-based catalysts face problems such as low selectivity, low activity, and poor stability, which severely restrict the practical application of carbon dioxide reduction technology.

[0004] Metal-organic framework materials are network structures formed by the self-assembly of metal nodes and organic ligands. They have abundant pore structures and high specific surface areas, which greatly promote the exposure of active sites. Organic ligands can regulate the electronic structure of metal active sites, further regulating the adsorption intensity of reaction intermediates. The easily tunable coordination environment (such as the metal site spacing, the number and type of ligands) promotes the selective regulation of different carbon dioxide reduction products.

[0005] In 1990, Ian D. Williams et al. (DOI:10.1126 / science.283.5405.1148) first prepared Cu-BTC with a pore size of approximately 1 nm and a specific surface area of ​​approximately 917.6 m². 2 / g, Cu-O4 coordinated, Cu-Cu spacing of 0.2682nm, paddle-like Cu dimer structure.

[0006] In 2018, Edward H. Sargent et al. (DOI:10.1021 / jacs.8b06407) achieved an increase in the Faraday efficiency of ethylene from 16% to 45% by heat treatment to distort Cu-BTC copper dimers to form local asymmetric atomic structures and unsaturated coordination active sites.

[0007] In 2021, Wolfgang Schuhmann et al. (DOI:10.1002 / anie.202108313) used Cu-BTC carbonization to derive CuxOyCz catalyst, added a certain proportion of polytetrafluoroethylene to adjust hydrophobicity, reduce electrode wetting effect, reduce hydrogen evolution activity and increase the concentration of intermediates on the electrode surface, and the ethylene Faradaic efficiency reached 36%.

[0008] In 2021, Liqiang Mai et al. (DOI:10.1002 / anie.202112116) prepared defective Cu-BTC, a wheel-like Cu dimer with Cu-O3 coordinated structural unit. The low coordination active sites significantly improved the selectivity of hydrocarbon components in the product, with the Faraday efficiency of ethylene being less than 35%.

[0009] However, existing Cu-BTC materials are micron-sized octahedral bulk materials with a pore size of approximately 1 nm, which hinders the full exposure of active sites and weakens mass transfer efficiency. Although copper-based metal-organic frameworks exhibit unique properties for producing multi-carbon products such as ethylene and ethanol due to their suitable adsorption strength for intermediates in carbon dioxide reduction reactions, the inherent linear relationship of adsorption energy limits their selectivity for single products. Furthermore, copper-based metal-organic frameworks consistently demonstrate poor stability at the electrocatalytic reduction potential of carbon dioxide. These shortcomings significantly limit the application of electrocatalytic carbon dioxide reduction.

[0010] Therefore, there is an urgent need to develop a new copper-based metal-organic framework material to improve its performance in the electrocatalytic reduction of carbon dioxide. Summary of the Invention

[0011] The purpose of this invention is to overcome the problems existing in the prior art and provide a copper-based metal-organic framework material, its preparation method, and its application. The copper-based metal-organic framework material of this invention exhibits high ethylene Faradaic efficiency when used in the electrocatalytic reduction of carbon dioxide to ethylene.

[0012] To achieve the above objectives, the present invention provides a copper-based metal-organic framework material having a honeycomb-like spherical morphology.

[0013] The metal element in the metal-organic framework material is copper;

[0014] The organic ligand in the metal-organic framework material is pyromellitic acid;

[0015] Among them, the diameter of the spherical particles of the metal-organic framework material is 0.8-8 micrometers.

[0016] Preferably, the metal-organic framework material exhibits characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2° as determined by X-ray diffraction.

[0017] A second aspect of this invention provides a method for preparing a copper-based metal-organic framework material, the method comprising the following steps:

[0018] (1) A methanol solution of copper precursor is mixed with a methanol solution of trimesic acid to obtain a mixture; under sealed conditions, the mixture is placed in a reaction vessel for hydrothermal reaction to obtain a solid product;

[0019] (2) The solid product is washed and dried;

[0020] The volume of the mixture is 18-50% of the volume of the reaction vessel;

[0021] The concentration of the copper precursor in methanol solution is 40-100 mg / mL;

[0022] The concentration of the methanol solution of pyromellitic acid is 18-50 mg / mL.

[0023] The third aspect of this invention provides the application of the copper-based metal-organic framework material described in the first aspect or the copper-based metal-organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide to ethylene reaction.

[0024] The beneficial effects of the present invention through the above technical solution include:

[0025] The copper-based metal-organic framework material of this invention possesses a unique honeycomb-like spherical morphology that combines the advantages of two-dimensional nanolayers and three-dimensional hierarchical pores, and has a small size, which improves mass transfer efficiency and greatly enhances its catalytic activity. When applied to the electrocatalytic reduction of carbon dioxide to ethylene, the copper-based metal-organic framework material of this invention exhibits excellent stability and high ethylene selectivity, and can serve as a highly efficient catalyst for the electrocatalytic reduction of carbon dioxide to ethylene.

[0026] The preparation method provided by this invention is a simple one-step hydrothermal method to prepare the copper-based metal-organic framework material with a honeycomb spherical morphology as described in this invention. The preparation process avoids the complex processes of adding additional structure modifiers or sacrificial templates commonly found in existing preparation methods. It is simple to operate, has mild preparation conditions, low cost, high efficiency, and is easy to scale up, and has great application advantages and prospects. Attached Figure Description

[0027] Figure 1 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Example 1 of the present invention;

[0028] Figure 2 These are the X-ray diffraction patterns of the copper-based metal-organic framework materials prepared in Example 1 and Comparative Example 1 of this invention.

[0029] Figure 3 These are infrared spectrum comparison images of the copper-based metal-organic framework materials prepared in Example 1 and Comparative Example 1 of this invention;

[0030] Figure 4 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 1 of the present invention.

[0031] Figure 5 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 2 of the present invention.

[0032] Figure 6 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 3 of the present invention.

[0033] Figure 7 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 4 of this invention.

[0034] Figure 8 This is a comparison of the linear voltammetric characteristic curves of the copper-based metal-organic framework materials prepared in Example 1 and Comparative Example 1 of this invention for the electrocatalytic reduction of carbon dioxide.

[0035] Figure 9 The copper-based metal-organic framework material prepared in Example 1 of this invention is used for the electrocatalytic reduction of carbon dioxide, and the current-time curve and ethylene Faraday efficiency-time curve are shown. Detailed Implementation

[0036] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0037] In one aspect, the present invention provides a copper-based metal-organic framework material having a honeycomb-like spherical morphology;

[0038] The metal element in the metal-organic framework material is copper;

[0039] The organic ligand in the metal-organic framework material is pyromellitic acid;

[0040] Among them, the diameter of the spherical particles of the metal-organic framework material is 0.8-8 micrometers.

[0041] In the metal-organic framework material of the present invention, more than 80%, preferably more than 90%, of the particles are spherical in shape.

[0042] It should be noted that the sphere described in this invention can be a sphere in the narrow sense, or an imperfectly regular sphere, such as a quasi-sphere.

[0043] The morphology of the metal-organic framework material described in this invention was measured using a scanning electron microscope.

[0044] In this invention, the diameter of the spherical particles of the metal-organic framework material is 0.8-8 micrometers, preferably 1-5 micrometers. The smaller diameter of the spherical particles of the metal-organic framework material in this invention is beneficial for promoting efficient mass transfer and exposure of active sites.

[0045] The diameter of the metal-organic framework material described in this invention was obtained by scanning electron microscopy.

[0046] The honeycomb-like spherical morphology of the metal-organic framework material described in this invention refers to the overall spherical morphology that can be observed under a scanning electron microscope, such as... Figure 1 Figure b shows the spherical particles, which exhibit a uniformly distributed and interwoven layered porous structure under high magnification using a scanning electron microscope. Figure 1 Figure a in the middle.

[0047] According to the present invention, preferably, the metal-organic framework material has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2° as characterized by X-ray diffraction.

[0048] As can be seen from the XRD pattern, compared with the metal-organic framework material of Comparative Example 1, the metal-organic framework material of this invention has characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2°, which can be used as a reference. Figure 2 The use of metal-organic framework materials with this microstructure is beneficial for improving the ethylene Faraday efficiency in the subsequent electrocatalytic reduction of carbon dioxide to ethylene.

[0049] According to the present invention, preferably, the metal-organic framework material is characterized by Fourier transform infrared spectroscopy at 1711±15 cm⁻¹. -1 1285±15cm -1 1204±15cm -1 1178±15cm-1 and 992±15cm -1 It has a characteristic peak.

[0050] As can be seen from the infrared spectrum, compared with the metal-organic framework material of Comparative Example 1, the metal-organic framework material of this invention has a higher density at 1711±15 cm⁻¹. -1 1285±15cm -1 1204±15cm -1 1178±15cm -1 and 992±15cm -1 It has characteristic peaks, which can be referenced. Figure 3 This demonstrates that the coordination environment of the metal-organic framework material described in this invention changes during the preparation process, causing changes in the electronic structure of the metal active center, thereby enabling the regulation of the adsorption strength of different reaction intermediates and greatly improving the Faraday efficiency of ethylene.

[0051] According to the present invention, preferably, the metal-organic framework material is composed of interwoven nanolayers.

[0052] It is understood that the honeycomb pores in the honeycomb spherical morphology of the metal-organic framework material described in this invention are macropores formed by the interweaving of nanolayers, as can be seen from [reference needed]. Figure 1 This is beneficial for improving mass transfer efficiency, thereby enhancing catalytic activity.

[0053] According to the present invention, preferably, the thickness of the nanolayer is 10-80 nm, more preferably 20-60 nm. This indicates that the copper-based metal-organic framework material of the present invention is composed of interwoven two-dimensional nanolayers. The layered two-dimensional surface greatly increases the exposure of active sites, thereby further enhancing its catalytic activity.

[0054] The thickness of the nanolayer described in this invention was obtained by scanning electron microscopy.

[0055] A second aspect of this invention provides a method for preparing a copper-based metal-organic framework material, the method comprising the following steps:

[0056] (1) A methanol solution of copper precursor is mixed with a methanol solution of trimesic acid to obtain a mixture; under sealed conditions, the mixture is placed in a reaction vessel for hydrothermal reaction to obtain a solid product;

[0057] (2) The solid product is washed and dried;

[0058] The volume of the mixture is 18-50% of the volume of the reaction vessel;

[0059] The concentration of the copper precursor in methanol solution is 40-100 mg / mL;

[0060] The concentration of the methanol solution of pyromellitic acid is 18-50 mg / mL.

[0061] In the preparation method provided by this invention, a methanol solution of a copper precursor and a methanol solution of trimesic acid are combined. By controlling the filling degree of the mixture in the reaction vessel and the concentration of the methanol solution of the copper precursor, a copper-based metal-organic framework material with a honeycomb spherical morphology as described in the previous aspect of this invention is obtained. The copper-based metal-organic framework material of this invention is beneficial for improving mass transfer efficiency, thus greatly enhancing its catalytic activity. When applied to the electrocatalytic reduction of carbon dioxide to ethylene, it exhibits excellent stability and high ethylene Faradaic efficiency.

[0062] The present invention does not particularly limit the reaction vessel for the hydrothermal reaction described in step (1), and any reaction vessel capable of realizing the above-mentioned hydrothermal reaction can be used. The present invention uses a conventional hydrothermal reactor with a polytetrafluoroethylene liner as an example.

[0063] In existing technologies, under the premise of ensuring reaction safety, the larger the volume of the mixture in the reaction vessel, the better, in order to obtain more metal-organic framework materials. Typically, the volume of the mixture is 70-80% of the reaction vessel volume. However, in this invention, the volume of the mixture is 18-50% of the reaction vessel volume, preferably 20-40%, for example, it can be 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, or any value within any two of these ranges. This preferred embodiment facilitates the reduction of coordinated divalent copper nodes to cuprous metals by methanol vapor, resulting in a unique honeycomb-like spherical morphology and a new crystal structure after recrystallization.

[0064] In this invention, the concentration of the methanol solution of the copper precursor is 40-100 mg / mL, preferably 40-60 mg / mL. For example, it can be 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL, 65 mg / mL, 70 mg / mL, 75 mg / mL, 80 mg / mL, 85 mg / mL, 90 mg / mL, 95 mg / mL, 100 mg / mL, or any value within any two of these ranges. This preferred embodiment facilitates obtaining the copper-based metal-organic framework material with the morphology and distribution described in this invention.

[0065] According to the present invention, preferably, the concentration of the methanol solution of trimesic acid is 18-50 mg / mL, more preferably 20-30 mg / mL. For example, it can be 18 mg / mL, 20 mg / mL, 22 mg / mL, 24 mg / mL, 26 mg / mL, 28 mg / mL, 30 mg / mL, 32 mg / mL, 34 mg / mL, 36 mg / mL, 38 mg / mL, 40 mg / mL, 42 mg / mL, 44 mg / mL, 46 mg / mL, 48 mg / mL, 50 mg / mL, and any value within any range of any two of these values. This preferred embodiment is advantageous for obtaining the copper-based metal-organic framework material with the morphology and distribution described in the present invention.

[0066] According to the present invention, preferably, the mass ratio of the copper precursor to trimesic acid is 0.5-8.5, more preferably 1-3.5, for example, it can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, and any value within any range formed by any two of these values. This preferred embodiment is more advantageous for obtaining the copper-based metal-organic framework material with the morphology and distribution described in the present invention.

[0067] In this invention, the copper precursor can be a conventional choice in the art. Preferably, the copper precursor is selected from at least one of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, copper sulfate pentahydrate, copper sulfate hexahydrate, copper chloride, and cuprous chloride.

[0068] The present invention does not have any particular limitation on the mixing in step (1), and can be carried out with reference to conventional methods in the art.

[0069] According to the present invention, preferably, the conditions for the hydrothermal reaction in step (1) include: a temperature of 80-140℃, preferably 110-130℃, for example, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, and any value within any range formed by any two of these values; and a time of 12-120h, preferably 18-84h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h. The values ​​are 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h, 50h, 52h, 54h, 56h, 58h, 60h, 62h, 64h, 66h, 68h, 70h, 72h, 74h, 76h, 78h, 80h, 82h, 84h, 86h, 88h, 90h, 92h, 94h, 96h, 98h, 100h, 102h, 104h, 106h, 108h, 110h, 112h, 114h, 116h, 118h, 120h, and any value within the range formed by any two of these values. This preferred embodiment is beneficial for improving the ethylene Faradaic efficiency in the subsequent electrocatalytic reduction of carbon dioxide to ethylene.

[0070] Preferably, the method further includes: performing solid-liquid separation on the product of the hydrothermal reaction in step (1) to obtain a solid product.

[0071] This invention does not impose any particular limitation on the method of solid-liquid separation; conventional techniques in the field can be used.

[0072] The present invention does not particularly limit the specific conditions for washing, and can be carried out according to the methods in the art, washing until the solution is clear.

[0073] The present invention allows for a wide range of choices of detergents for washing, which can be conventional choices in the art. Preferably, the detergent is selected from at least one of water, methanol, ethanol, and acetone.

[0074] The present invention does not particularly limit the drying conditions in step (2), and can be carried out according to methods in the art. Preferably, the drying is vacuum drying.

[0075] In this invention, the solid product can be dried entirely, or a portion of the solid product can be dried from its surface downwards. Preferably, in step (2), based on the depth of the solid product, 40%, preferably 30%, of the solid product depth is dried from top to bottom along the surface of the solid product. This preferred embodiment further improves the ethylene Faradaic efficiency in the subsequent electrocatalytic reduction of carbon dioxide to ethylene reaction.

[0076] It is understandable that in step (2), sampling is performed from the surface of the solid product downwards, and the material within 40% of the depth of the solid product is sampled. That is, the material within 40% of the depth of the solid product from the surface of the solid product can be sampled arbitrarily.

[0077] Preferably, this method does not include the addition of structure modifiers and / or sacrificial template agents. By employing this preferred embodiment, the preparation method provided by the present invention avoids the complex processes commonly found in existing preparation methods, such as the addition of additional structure modifiers or sacrificial template agents. It is simple to operate, has mild preparation conditions, low cost, high efficiency, and is easy to scale up, demonstrating significant application advantages and promising prospects.

[0078] The structure modifiers and / or sacrificial template agents described in this invention are conventional choices in the art, and will not be described further here.

[0079] The third aspect of this invention provides the application of the copper-based metal-organic framework material described in the first aspect or the copper-based metal-organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide to ethylene reaction.

[0080] The present invention does not impose any particular limitations on the conditions for the electrocatalytic reduction of carbon dioxide to ethylene reaction, and can be carried out in accordance with conventional methods in the art.

[0081] The present invention will be described in detail below through embodiments.

[0082] In the following embodiments, the product detection method is as follows:

[0083] Gas product analysis: A gas chromatograph (Agilent 7890B) was used, equipped with a flame ionization detector and a thermal conductivity detector. The thermal conductivity detector detected hydrogen, and carbon monoxide was detected by the flame ionization detector after being hydrogenated in a methane converter.

[0084] Liquid product analysis: Using proton nuclear magnetic resonance (Agilent 700M), the cathode electrolyte was taken, heavy water was added to lock the field, and dimethyl sulfoxide was used as an internal standard.

[0085] Example 1

[0086] Solution A was prepared by dissolving 0.721 g of copper nitrate trihydrate in 17.5 mL of methanol; solution B was prepared by dissolving 0.352 g of trimesic acid in 17.5 mL of methanol. Solutions A and B were mixed at room temperature and transferred to a 100 mL reaction vessel lined with a stainless steel jacket and treated at 120 °C for 36 h, then cooled to room temperature. The solvent in the hydrothermal reaction product was removed using a dropper, and the residual solvent evaporated at room temperature to obtain a solid product. A sample of material within 30% of the solid product's depth was taken from top to bottom and washed with ethanol, then vacuum dried at 80 °C for 12 h to obtain a copper-based metal-organic framework material, denoted as HC-Cu-BTC.

[0087] An exemplary SEM image of the copper-based metal-organic framework material described in Example 1 is given, as follows: Figure 1 As shown, the copper-based metal-organic framework material has a honeycomb-like spherical morphology, and it is composed of interwoven nanolayers. The thickness of the nanolayers is approximately 30-50 nm. The diameter of the spherical particles in the metal-organic framework material is 1-5 micrometers.

[0088] An exemplary XRD pattern of the copper-based metal-organic framework material described in Example 1 is given, as follows: Figure 2 As shown, compared to Comparative Example 1, there are additional diffraction peaks at 8.3° and 17.0°, indicating the formation of a new phase. Some of the Cu-BTC crystal phase prepared in Comparative Example 1 also remains, corresponding to diffraction peaks at 9.6°, 11.8°, 13.5°, and 19.2°. That is, compared to Comparative Example 1, the crystal structure of the copper-based metal-organic framework material of this invention has undergone significant changes.

[0089] An infrared spectrum of the copper-based metal-organic framework material described in Example 1 is given as an example. Figure 3 As shown. It can be seen that, compared to Comparative Example 1, at 1711 cm... -1 1285cm -1 1204cm -1 1178cm -1 and 992cm -1 A distinct absorption peak was observed.

[0090] Example 2

[0091] Solution A was prepared by dissolving 0.81 g of copper nitrate trihydrate in 17.5 mL of methanol; solution B was prepared by dissolving 0.352 g of trimesic acid in 17.5 mL of methanol. Solutions A and B were mixed at room temperature and transferred to a 100 mL reaction vessel lined with a stainless steel jacket and treated at 115 °C for 72 h, then cooled to room temperature. The solvent in the hydrothermal reaction product was removed using a dropper, and the residual solvent was allowed to evaporate at room temperature to obtain a solid product. A sample of material within 30% of the solid product's depth was washed with methanol and then vacuum dried at 80 °C for 12 h to obtain a copper-based metal-organic framework material. The thickness of its nanolayer was 30-40 nm. The diameter of the spherical particles in the metal-organic framework material was 1.5-5 μm.

[0092] Example 3

[0093] Solution A was prepared by dissolving 0.607 g of copper nitrate hexahydrate in 12.5 mL of methanol; solution B was prepared by dissolving 0.392 g of trimesic acid in 12.5 mL of methanol. Solutions A and B were mixed at room temperature and transferred to a 100 mL reaction vessel lined with a stainless steel jacket and treated at 125 °C for 24 h, then cooled to room temperature. The solvent in the hydrothermal reaction product was removed using a dropper, and the residual solvent was allowed to evaporate at room temperature to obtain a solid product. A sample of material within 30% of the solid product's depth was taken from top to bottom and washed with deionized water, then vacuum dried at 80 °C for 12 h to obtain a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles in the metal-organic framework material was 1-6 μm.

[0094] Example 4

[0095] The method of Example 1 was followed, except that 1.750 g of copper nitrate trihydrate was used to obtain a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles of the metal-organic framework material was 1-6 micrometers.

[0096] Example 5

[0097] The method of Example 1 was followed, except that 0.875 g of pyromellitic acid was used to obtain a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles of the metal-organic framework material was 1-6 micrometers.

[0098] Example 6

[0099] The method of Example 1 was followed, except that the hydrothermal reaction temperature was 140°C, resulting in a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles of the metal-organic framework material was 2-8 micrometers.

[0100] Example 7

[0101] The method of Example 1 was followed, except that the hydrothermal reaction time was 120 hours, yielding a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles in the metal-organic framework material was 2-8 micrometers.

[0102] Example 8

[0103] The procedure was carried out according to Example 1, except that material within 60% of the solid product's depth was taken from top to bottom along the surface of the solid product, washed with ethanol, and then vacuum dried at 80°C for 12 hours to obtain a copper-based metal-organic framework material. The thickness of its nanolayer was 30-50 nm. The diameter of the spherical particles of the metal-organic framework material was 0.8-6 micrometers.

[0104] Comparative Example 1

[0105] Copper-based metal-organic framework materials prepared by existing technology

[0106] Dissolve 2.952 g of copper nitrate trihydrate in 40.5 mL of an ethanol-water solution (ethanol:water volume ratio 1:1) to prepare solution A; dissolve 1.713 g of trimesic acid in 40.5 mL of an ethanol-water solution (ethanol:water volume ratio 1:1) to prepare solution B; mix solutions A and B at room temperature and transfer the mixture to a 100 mL reaction vessel lined with a stainless steel jacket and incubated at 120 °C for 24 h, then cool to room temperature. Separate the reaction products from the hydrothermal reaction to obtain a solid product.

[0107] The solid product was washed with ethanol and then soaked in ethanol for two days, with the ethanol being replaced approximately every 10 hours. It was then vacuum dried at 80°C for 12 hours to obtain the classic octahedral bulk copper-based metal-organic framework material, denoted as Cu-BTC.

[0108] SEM image of the copper-based metal-organic framework material described in Comparative Example 1, as shown below. Figure 4 As shown, the Cu-BTC is a micron-sized octahedron.

[0109] The XRD pattern of the copper-based metal-organic framework material described in Comparative Example 1 is shown below. Figure 2 As shown, it is consistent with the Cu-BTC crystal structure reported in existing literature.

[0110] The infrared spectrum of the copper-based metal-organic framework material described in Comparative Example 1 is as follows: Figure 3 As shown, copper is completely coordinated with pyromellitic acid.

[0111] Comparative Example 2

[0112] The method of Example 1 was followed, except that the amount of methanol used to prepare the copper nitrate trihydrate solution was 7.5 mL, and the amount of methanol used to prepare the trimesic acid solution was 7.5 mL, to obtain a copper-based metal-organic framework material.

[0113] SEM images of the copper-based metal-organic framework material described in Comparative Example 2, as shown below. Figure 5 As shown, the particles mainly exhibit irregular bulk structures at the micron and nanometer scales.

[0114] Comparative Example 3

[0115] The method of Example 1 was followed, except that 40 mL of methanol was used to prepare the copper nitrate trihydrate solution and 40 mL of methanol was used to prepare the trimesic acid solution, thus obtaining a copper-based metal-organic framework material.

[0116] SEM images of the copper-based metal-organic framework material described in Comparative Example 3, as shown below. Figure 6 As shown, its morphology consists of uniform nanoparticles.

[0117] Comparative Example 4

[0118] The method was carried out according to Example 1, except that 0.721g of copper nitrate trihydrate was dissolved in 17.5mL of ethanol to prepare solution A, and 0.352g of trimesic acid was dissolved in 17.5mL of ethanol to prepare solution B, thus obtaining a copper-based metal-organic framework material.

[0119] SEM images of the copper-based metal-organic framework material described in Comparative Example 4, as shown below. Figure 7 As shown, its morphology is mainly composed of micron-sized bulk materials.

[0120] Test Example 1

[0121] 5 mg of the copper-based metal-organic framework material prepared in the examples and comparative examples was dispersed in 500 μL of anhydrous ethanol and sonicated for 15 min. Then, 20 μL of Nafion perfluorosulfonic acid resin solution was added, and the mixture was sonicated for 30 min to obtain a mixed solution. 60 μL of this mixed solution was drop-coated onto 1 cm × 1 cm carbon paper and allowed to stand at room temperature for 0.5 hours to dry, yielding a working electrode loaded with the copper-based metal-organic framework material, wherein the loading of the copper-based metal-organic framework material was 0.58 mg. Using a 1 cm × 1 cm platinum sheet as the counter electrode and Ag / AgCl (saturated KCl) as the reference electrode, a proton exchange membrane (Nafion 117) separated the anode and cathode chambers, allowing selective passage of cations from the anode into the cathode chamber. Electrocatalytic carbon dioxide reduction was tested in an H-type electrolytic cell with the above-mentioned three-electrode system, using 0.1 M KHCO3 solution as the electrolyte. Using pure carbon dioxide gas as the reactant, the gas flow rate was controlled at 30 mL / min by a gas mass flow meter. The results of the reaction for 1 h at a potential of -1.7 (V vs. reversible hydrogen electrode) are shown in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] As can be seen from the results in Table 1, the copper-based metal-organic framework material provided by this invention has a significantly higher ethylene Faraday efficiency when applied to the electrocatalytic carbon dioxide reduction to ethylene reaction.

[0126] Meanwhile, a comparative graph of the linear voltammetric characteristics of the copper-based metal-organic framework materials in Example 1 and Comparative Example 1 for the electrocatalytic reduction of carbon dioxide to ethylene is provided, as shown in the figure. Figure 8 As shown, compared with Cu-BTC in Comparative Example 1, HC-Cu-BTC in Example 1 can generate a larger current density at the same potential, indicating that HC-Cu-BTC in Example 1 has superior catalytic performance.

[0127] Exemplary examples are provided for the electrocatalytic reduction of carbon dioxide to ethylene using HC-Cu-BTC prepared in Example 1, including current-time curves and a schematic diagram of the ethylene Faradaic efficiency-time at a constant potential of -1.7 (V vs. reversible hydrogen electrode). Figure 9 As shown, the current density decreased only slightly during the 24 hours of operation, and the Faraday ratio of ethylene remained essentially the same. Therefore, the HC-Cu-BTC of Example 1 of this invention exhibits good stability.

[0128] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A copper-based metal-organic framework material, characterized in that, The metal-organic framework material has a honeycomb-like spherical morphology; the metal-organic framework material is composed of interwoven nanolayers; the thickness of the nanolayers is 10-80 nm; the honeycomb pores in the honeycomb-like spherical morphology of the metal-organic framework material are macropores formed by the interwoven nanolayers. The metal element in the metal-organic framework material is copper; The organic ligand in the metal-organic framework material is pyromellitic acid; Among them, the diameter of the spherical particles of the metal-organic framework material is 0.8-8 micrometers.

2. The metal-organic framework material according to claim 1, wherein, X-ray diffraction characterization revealed that the metal-organic framework material exhibited characteristic peaks at 2θ of 8.3°±0.2° and 17.0°±0.2°. And / or, characterized by Fourier transform infrared spectroscopy, the metal-organic framework material has a wavelength of 1711±15 cm⁻¹. -1 1285±15 cm -1 1204±15 cm -1 1178±15 cm -1 and 992±15 cm -1 It has a characteristic peak.

3. The metal-organic framework material according to claim 1 or 2, wherein, The thickness of the nanolayer is 20-60 nm.

4. A method for preparing a copper-based metal-organic framework material according to any one of claims 1-3, the method comprising the following steps: (1) A methanol solution of copper precursor is mixed with a methanol solution of trimesic acid to obtain a mixture; under sealed conditions, the mixture is placed in a reaction vessel for hydrothermal reaction to obtain a solid product; (2) The solid product is washed and dried; The volume of the mixture is 18-50% of the volume of the reaction vessel; The concentration of the copper precursor in methanol solution is 40-100 mg / mL; The concentration of the methanol solution of pyromellitic acid is 18-50 mg / mL; This method does not include the addition of structure modifiers and / or sacrificial template agents.

5. The preparation method according to claim 4, wherein, The volume of the mixture is 20-40% of the volume of the reaction vessel; And / or, the concentration of the copper precursor in the methanol solution is 40-60 mg / mL; And / or, the concentration of the methanol solution of pyromellitic acid is 20-30 mg / mL.

6. The preparation method according to claim 4, wherein, The mass ratio of copper precursor to pyromellitic acid is 0.5-8.

5.

7. The preparation method according to claim 6, wherein, The mass ratio of copper precursor to pyromellitic acid is 1-3.

5.

8. The preparation method according to claim 4, wherein, The copper precursor is selected from at least one of copper nitrate trihydrate, copper nitrate hexahydrate, copper sulfate, copper sulfate pentahydrate, copper sulfate hexahydrate, copper chloride, and cuprous chloride.

9. The preparation method according to any one of claims 4-8, wherein, The conditions for the hydrothermal reaction in step (1) include: a temperature of 80-140℃ and a time of 12-120h.

10. The preparation method according to claim 9, wherein, The conditions for the hydrothermal reaction in step (1) include: a temperature of 110-130℃ and a time of 18-84h.

11. The preparation method according to any one of claims 4-8, wherein, In step (2), based on the depth of the solid product, material within 40% of the depth of the solid product is taken from top to bottom along the surface of the solid product for drying.

12. The preparation method according to claim 11, wherein, In step (2), based on the depth of the solid product, material within 30% of the depth of the solid product is taken from top to bottom along the surface of the solid product for drying.

13. The application of the copper-based metal-organic framework material according to any one of claims 1-3 or the copper-based metal-organic framework material prepared by any one of claims 4-12 in the electrocatalytic reduction of carbon dioxide to ethylene reaction.

Citation Information

Patent Citations

  • Preparation method and application of copper metal organic framework composite material

    CN113578271A